Central Visual Oscillopsia: Case Report and Review of the Literature. Issue 2 (June 2018) - Jones, Wallace; Silkworth, William; Dusto, Nathaniel; Pelak, Victoria S.; Berliner, Jean; Buard, Isabelle; Kluger, Benzi
Abstract : Here we present a patient with persistent central visual oscillopsia, review the literature on this condition, and report results from an experimental intervention using repetitive transcranial magnetic stimulation. A 57-year-old man reported persistent visual oscillopsia after a traumatic brain injury suffered 20 years earlier. Symptoms were presumed to be of cortical origin given his normal eye movements, eye stability, and peripheral vestibular function. Furthermore, he reported oscillopsia with visual imagery during eye closure. Occipital lesions damaging white matter connections identified on magnetic resonance imaging were suspected to be the cause of his symptoms. Repetitive transcranial magnetic stimulation was applied to the left extrastriate visual motion area V5/MT, to bilateral V5/MT, and to bilateral striate visual area V1. The primary outcome measure was dynamic visual acuity. Secondary outcome measures were gaze stabilization testing and subjective improvement as noted by interviews of the patient. Gaze stabilization and dynamic visual acuity testing revealed no difference between pre- and post-intervention with repetitive transcranial magnetic stimulation. The patient reported symptomatic improvement in large-amplitude oscillations that persisted for at least 12 months, but stated that smaller-amplitude oscillations were unchanged. Pathologies associated with central oscillopsia in the literature include neuromyelitis optica spectrum disorder, stroke, migraine without infarction, and psychological trauma. The patient's reported improvement in large- but not small-amplitude oscillopsia suggests that these symptoms may result from different neurophysiological mechanisms. Repetitive transcranial magnetic stimulation did not result in clinically significant improvement, suggesting a need for other strategies to treat this condition.